2012
DOI: 10.1504/ijepee.2012.048495
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth and tax structure in Zimbabwe: 1984-2009

Abstract: Abstract:We examine the tax-growth nexus in Zimbabwe using parametric and non-parametric analysis. We use a two-stage estimation procedure that first generates efficiency scores for the country using a Data Envelopment Approach. We use the efficiency scores in the second stage to normalise growth to get a proxy for potential economic growth. Using this potential growth we run a translog model that allows computation of time-varying elasticities of growth to changes in tax policy. The translog model results we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For example, the implementation of a self-assessment system in Malaysia is affected by tax knowledge (Palil and Mustapha, 2011). Whereas the tax policy in Zimbabwe negatively affected the economic growth during the period 1984-2009 (Marire and Sunde, 2012). The perceived fairness of the tax system is affected by corporate tax compliance (Puspita et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the implementation of a self-assessment system in Malaysia is affected by tax knowledge (Palil and Mustapha, 2011). Whereas the tax policy in Zimbabwe negatively affected the economic growth during the period 1984-2009 (Marire and Sunde, 2012). The perceived fairness of the tax system is affected by corporate tax compliance (Puspita et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies from Daselegn (2014), Ugwunta and Ugwuanyi (2015) presented a positive relationship between tax and economic growth. Marire and Sunde (2010), Keho (2013), Delessa (2014) and Saibu (2015) presented a negative relationship. Bonu and Pedro (2009) results shows no significant impact of income tax and Botswana's economic growth.…”
Section: Introductionmentioning
confidence: 95%
“…The theoretical framework and the bedrock of this study is underpinned on the social contract theory. The social contract theory was propounded by Lucke, Hobbes and Rousseau in the year 1690 (Marire & Sunde, 2009) in relation to the moral obligation that depends on written, verbal or implied agreements among parties in society. Clearly, the social contract is the unspoken agreement between individuals to give up certain natural rights in order to enjoy the benefits of society.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The social contract theory suggested that the society in any given community has the understanding and mutual consent to the existing morals and political set of behaviors, where each owed to the other some level of reciprocity and a reflection of a symbiotic relationship between each other. According to Marire and Sunde (2009), the social contract theory posited that people are in social morality and mutuality by choice and not by compulsion.…”
Section: Theoretical Frameworkmentioning
confidence: 99%